Potassium solubilization in phonolite rock by diazotrophic bacteria - Florentino, Ligiane Aparecida; Rezende, Adauton Vilela; Miranda, Cássia Cristina Bachião; Mesquita, Aline Carvalho; Mantovani, José Ricardo; Bianchini, Hudson Carvalho (Federal University of Piauí, 2017)
Some strains of nitrogen fixing bacteria, besides fixing the N2, can produce phytohormones, control pathogens, act in solubilization of minerals containing phosphorus (P) and potassium (K), contributing to plant growth. However, the solubilization of minerals containing K has been little exploited. Therefore, the aim of this study was to evaluate potassium solubilization (K) of phonolite rock by strains of associative nitrogen fixing bacteria supplied with two different carbon sources. Twelve bacterial strains were cultured for seven days at 25°C in Aleksandrov medium supplemented with phonolite rock powder. The experiment was carried out in a completely randomized factorial design, 13 x 2 (12 bacterial strains and a control without inoculation) and two carbon sources (glucose and sucrose) with four repetitions. After the growth, the supernatant was separated by centrifugation and analyzed for the final pH value and the content of K. All diazotrophic bacteria strains contributed to increase the release of K when compared to the control treatment. The strain UNIFENAS 100-94 solubilized 130 mg L-1 K in the presence of the two carbon sources, indicating the potential use of these diazotrophic bacterial strains for K solubilization from minerals.